KONFLIK KEPENTINGAN DALAM PENGELOLAAN MASJID BESAR KAUMAN YOGYAKARTA - Muhammad Chawari (Berkala Arkeologi, 2005)
With the large number of visitors that are almost evenly distributed every month of the year, of course, it will invite the people around the Kauman Grand Mosque to be able to take advantage of this opportunity, namely in the form of services. Activities in the form of services carried out by residents of the surrounding community, in a sense, will certainly "disturb" the preservation of the BCB (heritage). The forms of services provided by residents around the mosque include: lodging, bathroom services, street vendors, motorized vehicle parking services, buffers, and pedicab drivers. Over time, it is feared that their existence will lead to prolonged conflict and as a result it will interfere with the management (preservation and utilization) of this mosque in the future.